Estudo numérico de modelos de arrasto e do coeficiente de restituição no escoamento gás-sólido em leito fluidizado - Romero Luna, Carlos Manuel [UNESP] (2013)
Fluidized bed is an important unit operation of great interest in petroleum, chemical, metallurgical and energy industries. The large number of applications of fluidized bed in the industry and constant demand for improvements in the efficiency of the fluidization process, has produced an increase in the number of studies involving numerical simulations of gas-solid flow in fluidized bed through CFD. In numerical simulation, there is not yet an agreement on the selection of a drag model and in defining a suitable value for the coefficient of restitution. The purpose of this work was to study the influence of different drag models and restitution coefficient on the hydrodynamics of gas-solid flow in fluidized-bed, through numerical simulations. It is used a model based on the Eulerian-Eulerian approach considering a two-dimensional fluidized bed, which will be resolved using the open source MFIX code. To evaluate drag models, numerical results will be validated through the determination of the experimental data of Taghipour et al. (2005), which presents fluidized bed design parameters, such as fluidization curve, bed expansion, minimum fluidization velocity and void fraction profiles. It was also studied the effect of restitution coefficient on the hydrodynamics, through the development of a correlation in function of void fraction. The results demonstrated that drag model have an great influence in fluidized bed design parameters determination. In this study, a group of models were able to represent adequately the hydrodynamics, however Gidaspow (1994) drag model was the most accurate to represent the experimental data. Simulations were carried out considering restitution coefficient as a function of void fraction and using Gidaspow (1994) drag model. The simulation results obtained was able to improve the prediction of void fraction profile